(untitled) (Perner’s Contacts, 2008)
The paper deals with the questions of road transport of dangerous matters and the text is adverted to the risks sequent to this specific transport. The main goal is to advert to the risks possibly occurring in the case of traffic accident, but also to the risks occurring by the various logistic activities. There is endeavour to find the ways how to minimise these risks in the paper.